Mind the gap: Net incomes of minimum wage workers in the EU and the US - Ive Marx; Sarah Marchal; Brian Nolan (Institute for the Study of Labor (IZA), 2012)
This paper focuses on the role of minimum wages, tax and benefit policies in protecting workers against financial poverty, covering 21 European countries with a national minimum wage and three US States (New Jersey, Nebraska and Texas). It is shown that only for single persons and only in a number of countries, net income packages at minimum wage level reach or exceed the EU's at-risk-of poverty threshold, set at 60 per cent of median equivalent household income in each country. For lone parents and sole breadwinners with a partner and children to support, net income packages at minimum wage are below this threshold almost everywhere, usually by a wide margin. This is the case despite shifts over the past decade towards tax relief and additional income support provisions for low-paid workers. We argue that there appear to be limits to what minimum wage policies alone can achieve in the fight against in-work poverty. The route of raising minimum wages to eliminate poverty among workers solely reliant on it seems to be inherently constrained, especially in countries where the distance between minimum and average wage levels is already comparatively small and where relative poverty thresholds are mostly a function of the dual-earner living standards. In order to fight in-work poverty new policy routes need to be explored. The paper offers a brief discussion of possible alternatives and cautions against 'one size fits all' policy solutions.
urn:nbn:de:101:1-201208096248
Keywords: I3; H2; J8; 330; minimum wage; poverty; taxes; social transfers; subsidies; Mindestlohn; Wirkungsanalyse; Haushaltseinkommen; Armut; EU-Staaten; USA